Evaluation of Several Pup1-Lines of Rice (Oryza sativa L.) on Nutrient Solution and at the Field - Prasetiyono, Joko; Suhartini, Tintin; Soemantri, Ida Hanarida; Tasliah, ,; Moeljopawiro, Sugiono; Aswidinnoor, Hajrial; Sopandie, Didy; Bustamam, Masdiar (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
Phosphorus (P) deficiency is one of major problems in rice cultivation. Development of a tolerant variety to P deficient soil is expected to reduce the needs of P fertilizer. The aim of this research was to evaluate the agronomic performance of Pup1-introgression rice lines. This research consisted of two separate experiments, an evaluation on rice grown in nutrient solution in the greenhouse of ICABIOGRAD, Bogor; and field evaluation at upland rice screening site Taman Bogo, Lampung. The rice lines used were BC2 F3 derived from crossing of Situ Bagendit with Kasalath and NIL-C443, and from crossing of Batur with Kasalath and NIL-C443. Molecular analysis was conducted to verifiy the Pup1 introgression in the lines used and successfully confirmed the occurance of homozygote Pup1 segment in those lines. Evaluation of rice lines grown in nutrient solution was performed in a split plot factorial design, using the dose of Al (0 and 45 ppm Al3+) as main plots and dose of P (0.5 and 10 ppm P) as subplots. Field evaluation was performed in split plot design, with P fertilization (0 and 500 kg SP-18 ha-1) as main plots and BC2 F3 lines as the subplots. Evaluation using Yoshida nutrient solution showed that the BC2 F3 lines had greater total dry weight under low-P condition (37.5-112.5%), especially under Al-toxicity, compared to the respective parental varieties (Situ Bagendit and Batur). Field evaluation showed that the Pup1-introgression lines had greater shoot dry weight than the respective parental lines (10.5-74.82%). However there was no significnant effect of Pup1 introgression in terms of weight of filled grain.